2008
DOI: 10.11646/zootaxa.1913.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Phenacoccus solenopsis Tinsley (Sternorrhyncha: Coccoidea: Pseudococcidae), an invasive mealybug damaging cotton in Pakistan and India, with a discussion on seasonal morphological variation

Abstract: Since at least 2005, a possibly introduced mealybug of the genus Phenacoccus has been causing serious damage to cotton (Gossypium hirsutum) over much of the Sindh and Punjab districts of Pakistan and in north-western India. Some short papers have been published locally giving details on the structure and biology of this species and suggesting the name Phenacoccus gossypiphilous Abbas, Arif & Saeed (2005) but without designating type specimens or depositories. This name is here considered a nomen nudum. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
144
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(151 citation statements)
references
References 0 publications
4
144
1
2
Order By: Relevance
“…P. solenopsis has been described as a serious and invasive pest of cotton in Pakistan and India (Hodgson et al 2008) and on Hibiscus rosa-sinensis in Nigeria (Akintola and Ande 2008). Latest report on the invasiveness of P. solenopsis has been from the Eastern region of Sri Lanka (Prishanthini and Laxmi 2009) on ornamentals, vegetable crops, and weeds, and in China (Wang et al 2009; Wu and Zhang 2009) on cotton.…”
Section: Introductionmentioning
confidence: 99%
“…P. solenopsis has been described as a serious and invasive pest of cotton in Pakistan and India (Hodgson et al 2008) and on Hibiscus rosa-sinensis in Nigeria (Akintola and Ande 2008). Latest report on the invasiveness of P. solenopsis has been from the Eastern region of Sri Lanka (Prishanthini and Laxmi 2009) on ornamentals, vegetable crops, and weeds, and in China (Wang et al 2009; Wu and Zhang 2009) on cotton.…”
Section: Introductionmentioning
confidence: 99%
“…The growers' response was to use a tremendous amount of insecticides to manage the pest. Consequently, for example, in 2007, insecticides of US$ 121.4 million worth were used on cotton alone in only two months in Punjab (Hodgson et al, 2008). Moreover, previous studies (Khan et al, 2013b) revealed that the decision making by the farming community regarding the dose of pesticides and modes of action to manage insect pests largely depended on the availability, the amount of chemicals, and application equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The mealybug, Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae) is a devastating pest of cotton in different regions of the world such as Pakistan (Afzal et al, 2015;Hodgson et al, 2008), India (Nagrare et al, 2009), China (YanPing et al, 2009, United State (Kumashiro et al, 2001), Taiwan and Thailand (Hodgson et al, 2008), due to its polyphagous nature. This pest has a wide host range and causes economic damage to several crops including cotton, ornamentals, medicinal plants and vegetables (Abbas et al, 2010;Nagrare et al, 2009;YanPing et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in P. solenopsis establishment, abundance and damage potential P. solenopsis is a highly polyphagous species of mealybug, which damages more than 200 plant species across the globe (Williams and Granara de Willink, 1992;Abbas et al, 2005;Akintola and Ande, 2008;Hodgson et al, 2008;Ben-Dov, 2009;Nagrare et al, 2009;Vennila et al, 2010;Tanwar et al, 2007). Hence, the map of establishment risk index without the mask of production areas of cotton as a main host plant is quite reasonable when P. solenopsis host crops other than the cotton e.g.…”
Section: Discussionmentioning
confidence: 99%